Stereotypy and parkinsonism in tubercular meningitis: Expanding the spectrum - Shreyashi Jha; Mona Tiwari; Debarshi Chatterjee; Ashis Datta; Shobhana A (Annals of Movement Disorders)
Movement disorders associated with tubercular meningitis have been reported, ranging from tremors to chorea. Stereotypy is a rare manifestation following tubercular meningitis. Here we report a rare case of a 29-year-old man who developed stereotypy and parkinsonism following tubercular meningitis. The stereotypy was in the form of rotatory movements of the right upper limb, which were repetitive, purposeless, non-goal directed, present for most of the day, and partially suppressible. In addition, it was associated with severe generalized parkinsonism. This report expands the spectrum of movement disorders seen in tubercular meningitis.